Partitioning Evapotranspiration in Forested Peatlands within the Western Boreal Plain, Fort McMurray, Alberta, Canada - Gabrielli, Elise C. (Scholars Commons @ Laurier, 2016)
Forested peatlands in the Western Boreal Plain (WBP) represent hydrologically sensitive ecosystems that often support an open-crown forest of Picea mariana and/or Larix laricina. These systems store globally significant soil carbon, containing one-fourth to one-third of the world’s soil organic carbon pool (Turunen et al., 2002),serving a critical role in regulating atmospheric CO2. Recent studies indicate that the hydrological conditions are the critical determinant of a peatland’s carbon budget (Price et al., 2005; Aurela et al., 2007).To understand current hydrological conditions, it is essential to accurately estimate the rate of ET, due to its dominance within a peatland’s water balance (Price and Maloney, 1994; Fraser et al., 2001; Lafleur, 2008). The mechanism by which peatlands retain and exchange water with the atmosphere is important to maintain the stability of these systems. However, this stability is threatened by the impacts of both warmer and drier conditions associated with climate change, and altered hydroclimatic cycles as a result of landscape disturbance. Increasing drought (frequency and severity) has the potential to increase tree growth, modifying density, size and spatial arrangement of the trees (Kettridge et al., 2013). This expansion impedes incoming solar radiation from reaching the peat surface, potentially limiting surface evapotranspiration (ET), which at present, represents the main flux water loss from these systems. A reduction in surface ET(ETsurf)could further produce a reduction in total fen ET, despite predicted increases in canopy transpiration (T) attributed to the higher stem density. This research partitions ET between the canopy and understory between two typical fens, under current climate conditions, within the oil sands region of Fort McMurray, Alberta. The effects of climate, tree canopy and surface vegetation on the energy balance and ET processes were analyzed using a micrometeorology (MET) and eddy-covariance (EC) data in two typical Western Boreal Plain (WBP) ...